Biologically-guided isolation of leishmanicidal secondary metabolites from Euphorbia peplus L. - Elham Amin; Abeer Moawad; Hossam Hassan (Elsevier, 2017)
Leishmaniasis is a worldwide health problem, highly endemic in developing countries. Moreover, the severe side effects and the reported drug resistance make it an urgent need to search for effective drugs that can replace or supplement those currently used. In a research program designed to investigate the antileishmanial activity of plants collected from the Egyptian flora, twenty extracts from fifteen plants growing in Egypt have been investigated for in vitro leishmanicidal activity against Leishmania donovani promastigotes. Among the tested extracts, the methanol extract of Euphorbia peplus aerial parts exhibited a significant antileishmanial activity as it produced 100% inhibition of growth with activity similar to amphotericin B. The total extract was subjected to liquid-liquid fractionation using solvents of different polarities, followed by testing the antileishmanial activity of the successive fractions. Phytochemical exploration of the active n-hexane fraction (which produced 75% inhibition of growth) led to isolation of four compounds: simiarenol (1), 1-hexacosanol (2), β-sitosterol (3), and β-sitosterol-3-O-glucoside (4) from the biologically active sub-fractions. Structure elucidation was aided by 1D and 2D NMR techniques. In conclusion, E. peplus plant has many non-polar secondary metabolites that can be used as drug leads for treatment of leishmaniasis.